Dirty hands and social science - Sherman, Lawrence W. (Journal of research in crime and delinquency, 1993)
The author comments on a review by Stephen D. Mastrofski and Craig D. Uchida of the book Policing Domestic Violence: Experiments and Dilemmas. He claims that the book is about social science and some moral dilemmas it creates for policy analysis. In his opinion, the review offers no principles for drawing policy recommendations from mixed social science research and no plan for improving policing or reducing violence. He discusses the Minneapolis domestic violence experiment